The Lyon Terence : its tradition and legacy - Torello-Hill, Giulia; Turner, Andrew J. (Drama and theatre in early modern Europe, 2020)
"We first conceived of this study of the Lyon Terence in March 2016 when GTH, then a visiting fellow at Harvard University's Villa i Tatti research institute, proposed a jointly written, comprehensive monograph on it; as is argued in the introduction, despite the significance of this incunabulum for intellectual history hardly anything substantial has so far appeared on it in modern scholarship. Nevertheless, our engagement with this seminal book goes back several years before this. In 2010 AT assisted in identifying a single leaf of the Lyon Terence possessed by the Christchurch Art Gallery Te Puna o Waiwhetu in New Zealand, and drafted an online catalogue description for it, and subsequently the Gallery kindly gave us permission to use an image of this leaf on the cover of our jointly edited collection of studies Terence between Antiquity and the Age of Printing (Brill, 2015), in which we and our other contributors referred to this work at several junctures"--